Revisiting a Proposed Definition of Professional Service Firms - Zardkoohi, Asghar; Bierman, Leonard; Panina, Daria; Chakrabarty, Subrata (Academy of Management Review, 2011)
We have attempted to explain why professional service firms (PSFs) even in some of the most canonical examples (e.g., law firms) fail to follow the traditional definition. Growth in the size and geographic diversification of law firms has transformed their organizational structures and in some cases even allowed outside investment. We believe an attempt at defining organizational structure and ownership for any industry, including PSFs, is exposed to creating too many exceptions that may fall outside the confines of the definition. In particular, the problem of defining an industry is that while a given definition may in one context neatly correspond to the existing organizational structure and ownership, changes in the context can render the definition irrelevant over time. As an alternative to defining an industry, it might be more productive to examine how organizations and their respective industries become organized as contexts change.